Understanding hormonal and temporal factors associated with tomato (Solanum lycopersicum L. cv. Micro-Tom) acquisition of competence: key concepts for in vitro shoot regeneration - Notini, Marcela Morato (2017)
Plant regeneration through de novo organogenesis is a critical step in most of the plant micropropagation and genetic transformation procedures. In the last years, significant progress has been made in the understanding of the mechanisms underlying de novo organogenesis in the worldwide crop tomato (Solanum lycopersicum). However, the hormonal and molecular factors involving the acquisition of competence for tomato shoot formation, an essential step for the regeneration process, are still not known. The failure in acquire competence can be the reason for the widely described absence of shoot regeneration from tomato root explants. In the first chapter, we conducted a temporal and hormonal characterization of the tomato acquisition of competence and the shoot induction phases using the model system cv. Micro-Tom. Regeneration was improved by pre-incubation on root-inducing medium (RIM) during the early two days in culture, a period corresponding to acquisition of competence step in cotyledon explants. Conversely, the pre-incubation on another auxin-rich condition, the callus-inducing medium (CIM), under the same period, abolished the regeneration achievement. The 2d RIM pre-treatment induced an extensive and intense endogenous auxin response in the explant, probably improving the cells competence to produce shoots under further cytokinin induction on shoot-inducing medium (SIM). This knowledge was applied to improve the Agrobacterium-mediated tomato genetic transformation procedure, leading to an efficient, simple, inexpensive and genotype-independent protocol. In the second chapter, we developed an unprecedented method for tomato shoot regeneration from root explants. The shoot organogenesis was obtained by adjusting the CIM pre-treatment to the acquisition of competence period, corresponding to the initial four days in culture for root explants. The number and quality of shoots formed were also augmented by the optimization of explants properties, medium components, and culture conditions. Taken the two chapters together, the knowledge obtained about organogenic competence advanced and created new regeneration and genetic transformation systems, which are very useful tools for biotechnology and functional studies of specific genes in tomato.